Mother–child mutually responsive orientation and real‐time physiological coordination. Issue 7 (21st October 2021) - Hu, Yannan; McElwain, Nancy L.; Berry, Daniel
Abstract: From a biobehavioral framework, mother–child physiological and behavioral coordination are interdependent processes that contribute to children's socioemotional development. Little is known, however, about the temporal pattern of real‐time physiological coordination or its associations with global levels of mother–child behavioral coordination. We addressed these gaps using data from 110 mothers and their preschool‐aged children (56 girls, M age  = 53.63 months, SD  = 7.74) across two play tasks (i.e., puzzle, pretend play). Using indices of maternal and child parasympathetic response (i.e., changes in respiratory sinus arrhythmia [RSA]) across 15‐s epochs, we tested the extent to which within‐dyad physiological coordination was contingent on mutually responsive orientation (MRO; a global composite of behavioral coordination and shared positive affect assessed via observer ratings across each play task). Results from a series of two‐level coupled autoregressive models indicated that MRO moderated mother–lead RSA coordination, and this pattern emerged across both play tasks. Controlling for stability of within‐person RSA changes, increases in maternal RSA at time t  – 1 predicted increases in children's RSA at time t, but only for dyads averaging higher MRO during play. No interactions of MRO emerged for child–lead RSA coordination. Findings highlight the importance of dyadic behavioral processes for mother–child physiological coordination.